Pengaruh Motivasi Kerja, Lingkungan Kerja, Dan Semangat Kerja Terhadap Kinerja Pegawai Pada Dinas Pekerjaan Umum Kota Makassar - Fachruddin, Andi (Journal of Management Sains (JMS), 2024)
The purpose of this research is to (1) to know whether is any effect of motivation, working environment, and working spirit to the employee’s performance in the Department of Public Work in city of Makassar.(2)To know which one of the variable, that has the most dominant effect to the employee’s performance in the Department of Public Work in city of Makassar. This research is held in Department of Public Work of Makassar city. The population of this study are 80 of the employees of Department of Public Work in city of Makassar. The type of this research is descriptive qualitative with the random sampling method. And then, the data that we collect is processed using the regression analissis. The result of the research shows that all of the variable that have been studied simultaneously have significant effect to the employee’s performance in the Department of Public Work in city of Makassar. And the motivation variable has the most dominant effect